"We do STEM": Unsettled conceptions of STEM education in middle school S.T.E.M. classrooms. (13th November 2018) - Kloser, Matthew; Wilsey, Matthew; Twohy, Kyra E.; Immonen, Audrey D.; Navotas, Ariel C.
Abstract: STEM education has received attention both as a reform pedagogy and as a public means for economic growth and national security. Yet, despite this attention, clarity about what "counts" as STEM and how the individual disciplines relate to an integrated approach remains ambiguous. This article elicits the conceptions about what constitutes STEM education from middle grade teachers across the United States who teach a STEM discipline. Based on coded interviews and drawn conceptual models, participating teachers were more likely to describe essential aspects of integrated STEM found in the literature, but when asked to draw their conception of STEM education in their context, they often represented less ambitious conceptions. Furthermore, nontraditional subjects like engineering and technology were sometimes represented in subordinate ways to traditional subjects like science and mathematics. These findings have implications for preparing teachers to engage students in integrated STEM learning experiences as well as policy implications for what requirements must be in place to fund new STEM learning opportunities.